Crime and the labour market: evidence from a survey of inmates - Horst Entorf (Institute for the Study of Labor (IZA), 2009)
In this paper data from a survey of 1,771 inmates conducted in 31 German prisons provide microeconometric evidence on the relationship between individual anticipated labour market opportunities and the perceived probability of future recidivism. Results show that inmates with poor labour market prospects expect a significantly higher rate of future recidivism. Having a closer look at subgroups of prisoners reveals that drug and alcohol addiction cause adverse effects. Thus, improving prisoner health care by installing effective anti-drug programmes would be one of the most effective measures against crime.
urn:nbn:de:101:1-20090210151
Keywords: C83; J38; J68; K42; 330; Inmates survey; recidivism; job opportunities; illicit drug use; Kriminalität; Straftäter; Arbeitslosigkeit; Erwerbsverlauf; Erwartungstheorie; Diskrete Entscheidung; Deutschland